Peak-off-peak load shifting for hybrid power systems based on Power Pinch Analysis - Mohammad Rozali, N.E. (Elsevier Ltd, 2015)
Electricity load distribution tends to vary throughout the day depending on the time of operations of equipment and processes and the ambient weather conditions. Load shifting from peak to off-peak hours changes the electricity load profile and allows users to control the peak electricity demand and optimise the electricity cost. Power Pinch Analysis (PoPA) has been used recently to guide load shifting aimed at reducing the electricity maximum demand. This work applies the PoPA to optimise the overall electricity cost for a hybrid power system by performing cost-effective load shifting that takes advantage of the peak and off-peak electricity tariffs. Two new heuristics for load shifting have been proposed in this work. The results show that the total outsourced electricity during the peak hours has been successfully distributed to the off-peak hours to minimise the electricity cost. Â© 2015 Elsevier Ltd.